Enhancing Logistics Operations Using Blockchain Based Smart Contracts in ERP Systems - Percherla, Anand Kumar (International Journal of Computing and Engineering, 2025)
Purpose: The article aims to explore how blockchain-based smart contracts, when integrated into Enterprise Resource Planning (ERP) systems, can enhance efficiency, transparency, and security of logistics operations. It seeks to address the limitations of traditional ERP platforms and proposes a new model leveraging blockchain technology to overcome these issues. Methodology: The research adopts a comprehensive literature review and secondary data analysis approach. This involves: Synthesizing existing academic and industry knowledge, identifying key technological trends, evaluating challenges and benefits of implementing smart contracts within ERP systems. Findings: The integration of blockchain smart contracts with ERP systems can: Streamline key logistics processes such as procurement, shipment tracking, customs clearance, and proof of delivery. Enable automated payment settlements, real-time compliance validation, and fraud prevention in complex supply chains. Enhance real-time visibility, trust in multi-party transactions, and process integrity. Pose challenges related to technological architecture, interoperability, and implementation in platforms like SAP S/4HANA and Oracle ERP Cloud. Unique Contribution to Theory, Policy and Practice: Offers a synthesized view of how two advanced technologies can be integrated to evolve traditional supply chain theories around trust, decentralization, and process automation. The study provides insight into the regulatory and data governance implications of blockchain in enterprise systems. Highlights the need for updated compliance frameworks that accommodate smart contracts in logistics. It also presents actionable insights and use cases from industry case studies and pilot projects. Offers a roadmap for implementation, helping logistics enterprises understand how to practically adopt and scale blockchain-enabled ERP solutions. Discusses workforce transformation needed to support such digital initiatives.